Effect of resistance training combined with normobaric hypoxia in elite athletes - Galvin, H.; Sumners, D.; Bowtell, J.; Cronin, L.; Cooke, K. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Low intensity (<50% 1RM) resistance training combined with vascular occlusion induces similar increases in muscle mass and strength as high intensity (>70% 1RM) resistance training (1-2). Muscle hypoxia and metabolite accumulation appear to be important antecedents to these adaptations (3). Hypoxic interventions may provide a similar stimulus without the risk of thrombosis and the limited limb movement range and velocity associated with vascular occlusion. Certainly, recent studies of the acute and short-term responses of resistance training in environmental hypoxia have elicited improved markers of muscle growth and enhanced strength development (4, 5). Therefore the aim of this study was to examine the effects of resistance training combined with normobaric hypoxia using a single-blind randomized controlled trial design. Highly trained male rowers (n = 21) were randomly assigned into either a hypoxic (H) or normoxic (N) group. Maximal strength (1RM Bench and Leg press) and indices of muscular power (counter movement jumps (CMJ) and squat jumps (SJ)) were assessed before and after a three-week resistance training programme. The resistance exercise programme consisted of five exercises (Squat, Bench, Leg and Shoulder Press, Deadlift). The final exercise and a further 60 min seated rest were completed inspiring hypoxic (FIO2 = 13%) or normoxic (FIO2 = 20.9%) air. Salivary and capillary blood samples were collected pre and for 4 x 15 min intervals post training. Saliva was analysed for free testosterone and cortisol concentration and capillary blood samples were analysed for lactate concentration. Maximal strength increased in both groups (Leg press H: 12.2±6.0%; N: 10.1±7.2%, Bench press H: 10.7±7.6 %; N: 8.5±8.0 %) after the training period (p<0.001) but no significant differences were found between the two groups for maximal strength or power. Trends emerged indicating increases in muscular power in H compared to decreases in N (CMJ H: 2.8±9.8 %; N: -0.7±3.1 %; SJ H: 6.2±13.1 %; N: -2.0±5.2 %). There were no differences in salivary testosterone, cortisol or blood lactate concentration in the post exercise period between hypoxic or normoxic groups. Both groups had a significant increase in testosterone:cortisol ratio by week 3. Contrary to previous research, these findings suggest that in well-trained athletes hypoxia does not enhance the resistance training induced gains in maximal strength or power; nor does there seem to be any augmentation of the metabolic or hormonal responses to training.